Jek Nebenne! : A Method of Self-Healing in a Performance-Lecture - Hoirul Hafifi Arung (Institut Seni Indonesia Surakarta, 2021)
ABSTRACTThis artwork thesis depicts a multimedia performance, which combines several media such as photos, videos, sound recordings, installation, diagrams, charts, graphic design, and scientific journals, as well as digital cameras in performance-lecture. The creation practice borrowing the mode of a lecture combined with performance refers to